Experiment of Pullout Expansion Anchor in Installation Cast in Place and Post Installed with Concrete Breakout Failure - Huda, Amirul; Apriyatno, Henry (Jurnal Teknik Sipil dan Perencanaan, 2021)
Abstract: The use of anchors in construction is gaining popularity to connect steel and concrete constructions, and to transmit tensile loads acting onto the concrete. This research aims to find out the difference in the strength of anchor based on two methods of installations that are cast in place compared to post installed with the influence of effective depth, diameter of anchor and quality of concrete, and failure of concrete breakout. Expansion anchor used in this study is "Sanko" M12x100 and ready-mix concrete PT Bonindo Ungaran, fc 25 MPa with 6 pieces of test specimens of 300x300x150 mm. Each specimen has 4 anchors with a distance between the anchors of 100 cm, the distance between the anchors to the edge of the concrete 100 mm, and the depth of installation (hef) of 60 mm. The result of the study is the predicted value of the anchor pullout capacity with the failure of concrete breakout due to the theoretical pullout, namely 42,223 N, anchor pullout test results with cast in place method of 40,574 N and post installed method by 37,494 N. Tensile strength tests (material) of anchor (fy) 338 MPa, for flat concrete compressive strength strength of (f’c) 25,698 MPa. The results of the cast in place pullout test are larger and better than post installed (40574 N37494 N). Failure that occurred in cast in place method is a failure of concrete breakout and post installed method has occurred slip. Failures that occur are relevant to the theory.